Surface remineralization potential of casein phosphopeptide-amorphous calcium phosphate on enamel eroded by cola-drinks: An in-situ model study - Grewal, Navneet; Kudupudi, Vinod; Grewal, Sukrit (Contemporary clinical dentistry, 2013)
Aim: The aim of this study was to investigate the remineralization potential of casein phosphopeptide-amorphous calcium phosphate (CPP-ACP) on enamel eroded by cola drinks. Subjects and Methods: A total of 30 healthy subjects were selected from a random sample of 1200 children and divided into two groups of 15 each wherein calcium and phosphorus analyses and scanning electron microscope (SEM) analysis was carried out to investigate the remineralization of enamel surface. A total of 30 non-carious premolar teeth were selected from the human tooth bank (HTB) to prepare the in-situ appliance. Three enamel slabs were prepared from the same. One enamel slab was used to obtain baseline values and the other two were embedded into the upper palatal appliances prepared on the subjects′ maxillary working model. The subjects wore the appliance after which 30 ml cola drink exposure was given. After 15 days, the slabs were removed and subjected to respective analysis. Statistical Analysis Used: Means of all the readings of soluble calcium and phosphorous levels at baseline,post cola-drink exposure and post cpp-acp application were subjected to statistical analysis SPSS11.5 version.Comparison within groups and between groups was carried out using ANOVA and F-values at 1% level of significance. Results: Decrease in calcium solubility of enamel in the CPP-ACP application group as compared to post-cola drink exposure group (P < 0.05) was seen. Distinctive change in surface topography of enamel in the post-CPP-ACP application group as compared to post-cola drink exposure group was observed. Conclusion: CPP-ACP significantly promoted remineralization of enamel eroded by cola drinks as revealed by significant morphological changes seen in SEM magnification and spectrophotometric analyses.